1998
DOI: 10.1111/1467-839x.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Category of the Mind: Folk Psychology of Belief, Desire, and Intention

Abstract: According to the everyday understanding of the mind (called folk psychology), people's belief and desire causally combine to determine their intention, which in turn controls their action. However, recent empirical investigations have shown that psychologists' and laypeople's intuitions are not always in agreement about this common sense. To shed light, in this study folk psychology of belief, desire, and intention is conceptualized as a category of the mind; that is, a kind of category that embodies people's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…These findings offer support for the idea that action is determined by intention, which is determined by coherent beliefs and desires (Kashima et al, 1998). In summary, the general structure that emerges from empirical research conforms to the rational action model.…”
Section: Multiple Inference Modelsupporting
confidence: 67%
See 1 more Smart Citation
“…These findings offer support for the idea that action is determined by intention, which is determined by coherent beliefs and desires (Kashima et al, 1998). In summary, the general structure that emerges from empirical research conforms to the rational action model.…”
Section: Multiple Inference Modelsupporting
confidence: 67%
“…These conceptual analyses and empirical findings indicate that perceivers view actions within a framework of rational agency, assuming that actions realize goals (Gergely & Csibra, 2003;Kashima, McKintyre, & Clifford, 1998) and holding agents to conditions of rationality, coherence and consistency. Perceivers hold impressions of themselves and others to such conditions, preferring coherent accounts of beliefs, desires and intentions (Kashima, Yoshihisa, McKintyre, & Clifford, 1998).…”
Section: Rational Agencymentioning
confidence: 87%
“…Previous studies on the folk psychology of intentions have shown how desires and outcome beliefs relate to judgments of intention and action (e.g. Kashima et al, 1998;Malle, 1999Malle, , 2003. The studies here add to this research in several ways: First, they provide the first findings demonstrating how precondition beliefs affect judgments about goals and actions.…”
Section: Discussionsupporting
confidence: 56%
“…Previous research has shown that lay people regard beliefs and desires as being necessary for intentions (Kashima et al, 1998;Malle, 1999;Malle & Knobe, 1997), but none has shown that specific beliefs about preconditions influence participants' judgments about goals or intentions. The findings here clarify this issue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation